Exploring the Efficacy of U-Dictionary as a Digital Learning Tool for Vocabulary Acquisition: A Study in an Islamic Education Context - Sari, Dhian Marita; Pratolo, Bambang Widi (Journal of English Language and Education, 2024)
Many research studies have demonstrated the positive effects of utilizing u-dictionary as a learning media since this application is feasible to use, incredibly efficient, and has a variety of functions. U-Dictionary is one of the digital learning tools that are most compatible to use in a classroom setting that is entirely devoted to the study of vocabulary. This study aims to explore the impacts of u-dictionary learning media in teaching vocabulary as well as the opinions of students regarding the effectiveness of u-dictionary learning media in learning vocabulary. Subjects in the study consisted of forty-four students from two classes at STITMA that offer rigorous English instruction and are enrolled in Islamic education. The experimental group learned the target language through the use of u dictionary learning media, while the control group learned the same vocabulary using the more traditional method of instruction. Following the period of training, a vocabulary exam consisting of written questions on paper was given to both groups. As for the qualitative data, we acquired the students' viewpoints on u-dictionary through the use of a questionnaire, and brief interviews were employed as the method for collecting this information. The questionnaire was analyzed using the Likert scale, while the interview data was used to uncover new findings/phenomena from the study. The focus of the interviews was on the students' perspectives concerning the advantages and disadvantages of u-dictionary, as well as their suggestions for enhancing the effectiveness of using u-dictionary as a learning environment. These insights were obtained from the students' vocabulary test results, as well as their opinions and anticipations regarding the usefulness of u-dictionary.